Electroactivity of graphene oxide on different substrates - Bonanni, Alessandra (2013)
Graphene oxide is known to be electroactive on carbon materials due to the reduction of various inherent oxygen functionalities on its surface. In this work, we show that the characteristic reduction peak of graphene oxide is masked when the reduction is performed on different platforms (i.e. gold or platinum) apart from the usual carbon platform. Moreover, we demonstrated that the presence of gold nanoparticles (AuNPs) on the carbon platform has a strong influence on the reduction peak of graphene oxide nanoplatelets (GONPs). The influence of AuNP sizes and concentrations on the electrochemical reduction of GONPs was assessed as well. Finally, by XPS characterization we demonstrated that even though the reduction wave was not evident on the voltammogram, the reduction still occurred on the AuNP-modified carbon surfaces. Our findings can be very useful for those who are interested in exploiting the electroactivity of graphene oxide.